Capital at the Brink: Overcoming the Destructive Legacies of Neoliberalism - Leo, Jeffrey R. Di (Critical Climate Change, 2014)
Capital at the Brink reveals the pervasiveness, destructiveness, and dominance of neoliberalism within American society and culture. The contributors to this collection also offer points of resistance to an ideology wherein, to borrow Henry Giroux's comment, "everything either is for sale or is plundered for profit." The first step in fighting neoliberalism is to make it visible. By discussing various inroads that it has made into political, popular, and literary culture, Capital at the Brink is taking this first step and joining a global resistance that works against neoliberalism by revealing the variety of ways in which it dominates and destroys various dimensions of our social and cultural life. With essays by Paul A. Passavant, Noah De Lissovoy, Robert P. Marzec, Jennifer Wingard, Zahi Zalloua, Jodi Dean, Andrew Baerg, Jeffrey R. Di Leo, Christopher Breu and Uppinder Mehan.